PENGEMBANGAN AGROWISATA BERKELANJUTAN DI SEIN FARM (SEKEMALA INTEGRATED FARM) KOTA BANDUNG - Muhammad Fakhri Ramadhan; Muhammad Najih Fasya (Warta Pariwisata, 2022)
Development of the tourist industry in the Ujungberung District of Bandung City is focused on the Sein Farm's agrotourism concept (Sekemala Integrated Farm). According to the circumstances, there are issues with the implementation of commercial tourism, outreach, and education activities due to Covid-19 limitations, the lack of an integrated information system, a relatively small marketing scale, as well as the location of Sein Farm's limited accessibility by public transportation. The idea of integrated and sustainable agriculture is then examined using SWOT analysis, social, economic, and environmental analysis, and tourism activity analysis. The outcomes of these analyses are used to establish future strategy for the Sein Farm location.